IMPLEMENTASI PROGRAM PENGURUS MASJID BAITUL IZZAH DALAM MENINGKATKAN KESADARAN SHALAT BERJAMAAH (STUDI MASYARAKAT KOMPLEKS PERUMAHAN VILLA KENALI MAYANG MANGURAI KOTA JAMBI) - Tamirano , Randi; Zulqarnin, Zulqarnin; Hasanah, Neneng (UIN Sulthan Thaha Saifuddin Jambi, 2024)
This research is based on a reality that is concerning and requires attention, namely, the existence of a phenomenon or problem regarding the prosperity of the Baitul Izzah Mosque in the Villa Kenali Housing Complex, a community that is quite large but not proportional to the number of worshippers who come to the mosque to carry out congregational prayers. This encourages the author to put forward the purpose of this research, which is to find out the factors of the Mosque Management and Supporters in Inviting the Community in the villa housing complex to know the Congregational Prayer. The research approach used by the author is qualitative descriptive. Data collection was carried out by observation, interview and documentation techniques. The results of this study show the implementation of the Mosque Management program in Increasing Awareness of Congregational Prayers, conducting dawn studies, providing materials such as fiqh, moral creed, paying attention, forming yasinan groups. Inhibiting and Supporting Factors in Inviting the Community to Pray in Congregation. The busyness of the management in personal affairs is an obstacle to inviting the community to pray in congregation, low religious knowledge of the community, the absence of a youth yasinan mobilizer, holding religious lectures and discussions. The solution carried out is that the Mosque Management in Increasing Awareness of Congregational Prayer has exemplified good attitudes and behaviors to the congregation, held a dawn study program, paid attention to the community and invited the community to pray in congregation at the mosque, complete facilities and infrastructure, as well as a better form of program implementation, so that with the program it fosters a sense of awareness of the congregation to continue to pray in congregation in mosque.